NARRATION AS A MEANS OF COMMUNICATION IN SELECTED NOVELS BY J.M.COETZEE: WAITING FOR BARBARIANS AND FOE - Jihad Jaafar Waham; Wan Mazlini Othoman (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2019)
Narrations become very important such that, we tend to try to make others want to fit into them to identify with us, which is why narrative is often used in the recount of events, the past, geared to justify the systems of domination and control evident in the plight of South Africans during the apartheid period. Moreover, the narrative also shelters realities against which the truth can be judged, and they also have some sense or measure of proper world order, against which moral action can be judged. As such, narration point of view can also be determined through the perspective the story is being told. Be it the first person narrative where the author or narrator refers to himself with the personal pronoun of I, me, my, myself, however, this mode of narration may also use second and third-person pronouns in addition to the first-person point. Wherefore, the second Person narrator sees the author or narrator addresses the reader directly as you, and may use the words we and us as well in the process. The third person pronouns still could be used in a novel, in addition, where the narrator or author refrains from using a first or second person and only refers to characters as he or she or it to demonstrate his narrative techniques in this process. To this effect narrative technique employed by J.M. Coetzee’s as accounted in the selected novels used for this paperwork to explore Coetzee’s capabilities of developing a true sense of self as well as communicate to others through the Narration